Low cost Passive Monitoring of Nitrogen dioxide and Sulphur dioxide in ambient air - Byanju, R. M.; Gewali, M. B.; Manandhar, K. (Journal of Nepal Chemical Society, 2012)
Standard nitrogen dioxide (NO2) and sulphur dioxide (SO2) monitoring techniques require expensive instrumentation which is not easily adapted for large scale monitoring by resource limited countries. This paper presents the use of locally available relatively cheaper polyethylene tubes to be developed as passive diffusive sampler and use for monitoring of ambient nitrogen dioxide and sulphur dioxide using Triethanolamine (TEA) as absorbent. After extraction with double distilled water, modified Griese-Saltzmann method and West-Gaeke method were used for analysis of nitrite and sulphate adduct formed due to reaction of NO2 and SO2 respectively with TEA using spectrophotometer. The results are successfully compared with other standard methods. The detection limits and precision of the method as expressed as Coefficient of variation are good enough for monitoring of NO2 and SO2 in ambient air. DOI: http://dx.doi.org/10.3126/jncs.v27i1.6439 J. Nepal Chem. Soc., Vol. 27, 2011 34-45 Uploaded date: 16 July, 2012